Spiritual Emotional Freedom Technique Decreasing Stress on Patients with Cervical Cancer - Desmaniarti Z,; Nani Avianti (Jurnal Ners, 2014)
Introduction: Cervical cancer is known as one of deadly disease. The global incidence of cervical cancer is the second largest in the entire world, including in Indonesia. RSUP Dr. Hasan Sadikin Bandung, cervical cancer ranked fi rst (62.27%) compared with other fi ve types of obstetry and gynecology malignancies (suspected malignant ovarian tumors 16.12%, ovarian cancer 11.76%, vulva cancer 8.65% and endometrial cancer 1.19%) (Destiana, 2012). Chemotherapy as one of cancer treatment causes various side effects include hair loss, nails blackened, nausea and vomiting, that could makes patient stressful. SEFT ( Spiritual Emotional Freedom Technique ) is useful to overcome negative emotions through a combination technique that uses psychological energy, spiritual strength, and praying. SEFT is an effective intervention in manage stress, there are some techniques that practiced simply such as praying, NLP (Neuro Linguistic Programming), hypnotherapy, visualisation, meditation, relaxation, imagery and desensitisasi (Zainuddin, 2008). The purpose of this study was to explain reducing stress on patiens with cervical cancer through Spiritual Emotional Freedom Technique (SEFT) at RSUP Dr. Hasan Sadikin Bandung. Improvements on patient’s stress will lead to a better result on cervical cancer therapy.Methods: This study was used quasy experiment pre-post test randomize control group design. Patient with cervical cancer at stadium I to III that taking chemotherapy was selected by using purposive sampling and divided into two groups. Each group contains 34 patients. Intervention group was given SEFT in three round. Each round took 30 minutes. Before and after intervention patients was given Questionnaire. The data were analyzed using paired t-test and independent t-test.Result: The result of this research showed that patient’s stress getting lower signifi cantly after intervention.Conclusion: SEFT could reduced stress on patients with cervical cancer that taking chemotherapy at RSUP Dr. Hasan Sadikin Bandung.